2005
DOI: 10.1227/01.neu.0000156644.45384.92
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Cerebral Vasospasm in Patients Presenting with Aneurysmal Subarachnoid Hemorrhage: A Review

Abstract: To date, a large blood burden is the only consistently demonstrated risk factor for the prediction of cerebral vasospasm after SAH. Because vasospasm is such a multifactorial problem, attempts to predict its occurrence will probably require several different approaches and methodologies, as is done at present. Future improvements in the prevention of cerebral vasospasm from aneurysmal SAH will most likely require advances in our understanding of its pathophysiology and our ability to predict its onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
126
3
10

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(142 citation statements)
references
References 168 publications
3
126
3
10
Order By: Relevance
“…A comprehensive review of the literature by Harrod et al from 1996Harrod et al from to 2005 showed that the only factor that has shown to be predictive of cerebral vasospasm is the burden of blood at the time of SAH. 3 A previous study from our center corroborates this finding and stratifies the maximum clot burden into 5 categories.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…A comprehensive review of the literature by Harrod et al from 1996Harrod et al from to 2005 showed that the only factor that has shown to be predictive of cerebral vasospasm is the burden of blood at the time of SAH. 3 A previous study from our center corroborates this finding and stratifies the maximum clot burden into 5 categories.…”
Section: Discussionsupporting
confidence: 84%
“…3,5,10 Identifying patients at the greatest risk for cerebral vasospasm is an important prognosticator in the setting of SAH and may identify patients who will likely need hypertensive therapy, or potential endovascular treatment of vasospasm, or both. A comprehensive review of the literature by Harrod et al from 1996Harrod et al from to 2005 showed that the only factor that has shown to be predictive of cerebral vasospasm is the burden of blood at the time of SAH.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of compounds in the first class would be hemoglobin (Hb)and BOXes, and examples in the second class of compounds would be endothelin or nitric oxide (Figure 2), which could be directly or indirectly induced by the BOXes. The rationale that blood itself or some metabolite of components of blood cause vasospasm is compelling since this helps explain why vasospasm tends to occur where large blood clots occur around vessels at the base of the brain (Harrod et al, 2005;Kistler et al, 1983).…”
Section: Two Classes Of Compounds That Could Cause Vasospasmmentioning
confidence: 99%
“…In all, 25% of patients die almost immediately after hemorrhage due to arrest of the cerebral circulation caused by acute intracranial hypertension as a consequence of the evolving hematoma (Pobereskin, 2001). Out of the remaining 75% of SAH victims, 15% die with a significant delay of several days (due to delayed cerebral ischemia or cardiopulmonary reasons); however, the remaining 60% of patients die within 48 h of the initial bleeding (Weir et al, 1978;Harrod et al, 2005) due to rebleedings (25%) or a sequence of events summarized by the term ''Early Brain Injury'' (EBI; 35%) (Pobereskin, 2001). While rebleedings can be prevented by surgical or endovascular procedures and, after years of research, new therapeutic options are emerging for the intriguing phenomenon of delayed cerebral ischemia, no treatment is available for EBI and its underlying mechanisms have only recently started to be understood (Cahill and Zhang, 2009;Pluta et al, 2009).…”
Section: Introductionmentioning
confidence: 99%